Risco regulatório: uma análise sobre a volatilidade dos retornos das ações da sabesp no período de 2007 a 2015 - Silva, Luciano Ferreira da (2016)
Although the search for strenghtening regulation and control had only been explicited in the 1995 with the Managerial Reform of Ministry of Government Administration and Reform (MARE), through State's managerial reform master plan, the basic sanitation sector only achieved federal regulatory landmark with the 11.445/2007 law. This law has brought universal access to services as one of the fundamental principles and objectives pursued by organizations related to this sector, which, after analyzing financial resources needed, estimated by the Ministry of Cities in 2013, would be inconceivable without the participation of private capital. On the other hand, introducing private capital necessarily improves regulatory action, once the more transparent and stable are the rules and mechanisms behind regulatory agencies, the greater are the chances of return to investors and the impacts on cost of companies’ capital are smaller. Thus, assessment of risk impacts derived from the action of regulatory agencies is of fundamental importance to the awareness of the need for greater transparency predictability and stability of the rules. Thus, whereas the Basic Sanitation Company of the State of São Paulo (Sabesp), is commonly used as a benchmark for the sector, among other reasons because it is the largest segment, this study examined the effects of Resolutions of the Regulatory Agency of sanitation and Energy of the State of São Paulo (Asesp), the regulatory events, of economic and financial nature, from 2007 to 2015, on the clusters of volatility of return of sanitation Company shares Basico do Estado de Sao Paulo (Sabesp ) by the method TGARCH (Threshold Generalized Autoregressive Conditional Heteroscedastic). The results constitute evidence that the regulatory agency decisions can influence the volatility when it generates change in expectations and may cause changes in the risk and cost of capital. At the end has crafted a diagnosis that considered correct use of the CAPM and WACC to define the cost of capital, but pointed out that the decision of Arsesp in not recognizing a specific component for regulatory risk was inadequate. Recommends to the next tariff review cycle of Sabesp, the assessment by the Arsesp of possibility of including a specific component to reward investors due to regulatory risk.